Implikasi Wujud Al-Dzihni dalam Persepsi Sensual: Kritik Terhadap Empirisisme dalam Perspektif Wujud al-Dzihni - NAZHORI AUTHOR (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2016)
This article describes the process of how knowledge is formed and formulated with sensory perception in the form of experience. In Islamic philosophy, sensory experience that generates knowledge has never happened in the absence of mental existence as one of the essential principles of the philosophy of Mulla Sadra. Al- though the sensory perception is not the only one, Sadra considers that acceptable reason as sensory observation is a result of the unity of subject and object. This concept provides a basis for thinking that any form of authenticity from fundamen- tal ideas give meaning to the doctrine of the other. Without that sense, perception will never be materialized. This perception involves the awareness that comes from the soul as an active agent. Rejecting perception means the rejection of the value of knowledge. In Mulla Sadra’s argument, the implications of mental concepts in the sensual perception will influence sense objects.